POPULASI GAJAH SUMATERA (Elephas maximus sumatranus Temminck) DI BAGIAN TIMUR LAUT TAMAN NASIONAL TESSO NILO PROVINSI RIAU - Umum Juwanto; Defri Yoza; Viny Volcherina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2020)
Tesso Nilo National Park (TNTN) is one of the national parks in Indonesia located in Riau Province. The TNTN area is a habitat for several animals and one of which is the sumatran elephant (Elephas maximus sumatranus Temminck). Sumatran elephant is one of the largest land mammals on earth and is an animal protected by Indonesian law Number 5 of 1990. The purpose of this study was to determine the population of sumatran elephants in the TNTN northeastern area. The benefit of this research is to provide relevant information about the Sumatran elephant population in the TNTN area. The method used for this research observation is the transect line method and made in 4 different locations. in this study 49 elephants were found from 4 research locations. The highest number was found on the Restoration Camp track, which is 19 elephants, while the smallest number is in Lubuk Kembang Bunga Village track, which is 2 elephants. For population density, the highest density was found in the Restoration Camp with a density of 1,87/km², while the smallest density was found in Lubuk Kembang Bunga Village with a density of 0,12/km²